Factors affecting business success of small and medium enterprises in Malaysia / Azlin Shafinaz Arshad ... [et al.] - Arshad, Azlin Shafinaz; Mohd Zain, Zahariah; Arshad, Afiza Azura; Md Kamil, Norliani (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2017)
The aim of this study is to determine the factors affecting the business success of Small and Medium Enterprises (SMEs) in Malaysia and to identify which of these factors affects the business success of SME the most. A set of questionnaire has been distributed to SMEs located in Negeri Sembilan in which only 120 questionnaires were usable. Descriptive analysis was conducted to analyze the data specifically using Pearson correlation as well as Multiple Regression Analysis. The R square value for this study is 0.811 which is considered very high and means that the multicollinearity is a potential problem. Hence, Variance Inflation Factor (VIF) was conducted to detect the severity of multicollinearity and it was found that multicollinearity is not serious. The multiple regression analysis results indicate that all three variables appear to be significant and have influence toward the business success of SMEs in Malaysia This study provides a greater understanding of factors affecting the business success of SMEs.